منهجيّةُ الإمامُ علي (عليه) في مواجهةِ المنحرفينَ عنهُ والخارجينَ عليّه - الموسوي, جاسم حسن جابر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Imam Ali's (peace be upon him) thoughts and behaviors in his struggle with his opponents created a unique context, characterized by their connection to the Qur'an and the fundamentals of Islam, on the one hand, and their ability to be recorded across time and space, on the other, for a special production with characteristics and orientations that represent the spirit of an evolving Islam, firmly rooted in justice and creativity. Creativity is a value-based and humane dimension, free from innovation and deviation. The most important of these are highlighted below Not to accuse someone of unbelief, and refrain from treating them in kind except to the maximum extent after exhausting all possible means, and his derivation of legal rulings in fighting the people of the Qiblah known as (the rulings of rebels) , and there is no spoils of war for someone who has no group, and there is no retaliation in sedition And legitimate practices that were previously unknown to Muslims, all stemming from the Kingdom of God, which God has drawn as a separation between hypocrisy and faith, and His ideal and renewed applications of religion in building life.